2022
DOI: 10.3390/pr10101955
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation Study on the Flow Properties of Materials for Plugging While Drilling in MWD

Abstract: The method of plugging while drilling has been one of the commonly used methods to control formation loss during drilling. The damage to materials for plugging while drilling to MWD has become a complex problem. For many years, field engineers had insufficient knowledge of the passing performance of materials for plugging while drilling in measurement while drilling (MWD). In the existing research, the blocking mechanism of materials for plugging while drilling to mud screen during the flow process is still un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…However, when the particle size reaches 2 mm, a significant portion of the particles tend to accumulate at the entrance of the fracture, resulting in a limited support effect for fracture plugging. Hence, based on experimental findings, it can be concluded that particles with a size equivalent to half of the fracture width exhibit superior suspension and sealing capabilities [20,21].…”
Section: Effect Of Plugging Particle Sizementioning
confidence: 99%
“…However, when the particle size reaches 2 mm, a significant portion of the particles tend to accumulate at the entrance of the fracture, resulting in a limited support effect for fracture plugging. Hence, based on experimental findings, it can be concluded that particles with a size equivalent to half of the fracture width exhibit superior suspension and sealing capabilities [20,21].…”
Section: Effect Of Plugging Particle Sizementioning
confidence: 99%